Konsep Pengendalian Inflasi dalam Perspektif Al-Qur’an - Iryanto, Muhammad; Abubakar, Achmad; Inat, Fathy (AL QUDS : Jurnal Studi Alquran dan Hadis, 2023)
The Concept of Inflation Control in the Perspective of the Qur'anThis study aims to understand the concept of inflation control in the perspective of the Qur'an, using Tafsir Maudhu'i and analyzed with an analytical descriptive approach to examine the symptoms of inflation and the causes that are the background of inflation. The findings of this study confirm inflation as a symptom of economic disequilibrium that brings damage. Any damage (in whatever form) caused by human hands is condemned by the Qur'an. While the contemporary economic system exhibits ribawi-speculative practices that are driven by excessive consumption desires. As a result, inflation with its destructive power is difficult to avoid.The Qur'an and the Sunnah of the Holy Prophet (peace be upon him) as a guide to life lead to make changes towards balance for the good of mankind. The Qur'an calls on people to return to the right path, which is to represent the consciousness of the balance of life in the world and the Hereafter according to the guidance of the Qur'an and the Sunnah of the Holy Prophet (peace be upon him). By striving to build new empirical facts in the form of an economic system with an objective balance of justice: interest-free and speculation-free, expenditure control, and consumerism restraint. This value foundation supports operational policy to control inflation through fiscal and monetary instruments